The incorporation of a series of acrobatic movements into the training regimen of gymnasts - Udalova M.A.; Morozova L.V.; Kiryanova L.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to theoretical foundation for acrobatic training in rhythmic gymnastics, creating a comprehensive set of acrobatic exercises through the integration of non-objective training methods. Methods and structure of the study. Examination of literary materials and pedagogical observation of gymnasts’ training sessions. The study focused on gymnasts in the sports improvement and advanced sports categories, who were training under the CMS and MS programs. Results and conclusions. The article provides a scientific rationale for the significance of acrobatic training in rhythmic gymnastics. The article outlines the methods and presents a collection of acrobatic exercises that are based on the integration of non-objective training techniques.